The effect of adding ytterbium trifluoride on the radiopacity, compressive strength, setting time and bioactivity of biodentine: an in vitro study - Bahaa, Nareman Mahmoud; El-Korashy, Dalia Ibrahim; Sherief, Dalia Ibrahim (Brazilian Dental Science, 2022)
Objective: This study aimed to evaluate the radiopacity, compressive strength, setting time and bioactivity ofBiodentine after modification with Ytterbium Tri-Fluoride (YbF3) in three different concentrations. Material andMethods: Radiopacity was determined using the equivalence in millimeters of aluminum (mm Al) from digitalradiographs. Compressive strength was evaluated using a universal testing machine. The initial and final settingtimes were evaluated using Gillmore needle. The bioactive potential was evaluated using the environmental scanningelectron microscope (ESEM) connected with Energy Dispersive X-ray analysis (EDX) and X-ray Diffractometer(XRD) at three different time intervals. pH was measured using a pH-meter. Data were analyzed using one-wayANOVA followed by Tukey’s post hoc tests (P< 0.05). Results: Radiopacity of Biodentine with 2.5%, 5% and 7.5%YbF3 was significantly higher than unmodified Biodentine (P < 0.05). Unmodified Biodentine showed the highestmean compressive strength values compared to all other groups (p< 0.05). The addition of YbF3 to Biodentine hasextended the final setting time except for the 2.5% YbF3 group that showed no significant difference comparedto the control. All groups showed an alkaline pH at 28 days, ESEM coupled with EDX analysis showed evidenceof dense globules of calcium phosphate on the surface indicating enhancement of bioactivity. Conclusion: 2.5%YbF3 can be a promising radiopacifying agent to Biodentine with improvement in radiopacity, bioactive potentialand maintaining the setting time and compressive strength at acceptable level as indicated by the ISO standards.KEYWORDSYtterbium trifluoride; Radiopacity; Biodentine; Bioactivity.